Preparation of poly(urethane-urea) nanoparticles containing açaí oil by miniemulsion polymerization - Valério,Alexsandra (2013)
Polyurethane nanoparticles (NPs) are promising candidates for the controlled and targeted delivery of therapeutics in a variety of biomedical applications. In this work, a report is made of NPs produced by miniemulsion polymerization with isophorone diisocyanate (IPDI) and castor oil, glycerol, and poly(ethylene glycol) (PEG) with molar masses 400 and 1000 as monomers and Tween 80, Span 80 and Lutensol AT 25 as surfactant and açaí oil as costabilizer. Stable dispersions with sizes between 100 - 500 nm were achieved. The effects from polyol, types and concentration of surfactant and reaction temperature on the size of the NPs and weight average molar mass were evaluated. Morphological characterization was accomplished using images from Transmission Electron Microscopy (TEM) and Scanning Electron Microscope (SEM).